Knowledge And Practices Regarding Mosquito Borne Disease Among People of An Urban Area in Kalaburagi, Karnataka - Tenglikar, Pallavi V; Hussain, Mubeen; Nigudgi, SR; Ghooli, Shreeshail (National Journal of Community Medicine, 2016)
Introduction: The mosquito borne diseases poses an immense public health concern and also a growing urban problem. For developing a suitable and effective health education strategy, it is inevitable to understand the level of knowledge of the community, and practices regarding mosquito borne diseases. Methods: The present study was carried out in an urban field practice area of M. R. Medical College, Kalaburagi, Karnataka. A total of 247 houses were selected for study by systematic random sampling. Data was collected using a semi-structured questionnaire during transmission season of vector borne diseases. Results: Out of the 247 studied population, majority 171(69.23%) knew that malaria is transmitted by mosquito followed by 68(27.53%) Filarial, 22(8.91%) dengue and 37 (14.98 %) Chikungunya. 85.02% participants answered dirty stagnant water as mosquito breeding place. Regarding source of knowledge majority 153(61.94%) was from Television followed by 135(54.66%) from Health care providers Conclusion: Community participation in terms of knowledge and practice regarding vector control is deficient at places & needs to be addressed for effective mosquito control.